Relationship between Knowledge and Preparedness Levels of ER Staff on Pre-Triage System Implementation - Yuvita, Emilda; Fitriasari, Nikma; Harjayanti, Nofita Dwi (Jurnal Kedokteran Brawijaya, 2021)
The Emergency Department (ED), as the main entrance of health service access in hospitals, faces the highest infection risk and high service load due to the increasing number of patients during the Covid-19 pandemic. Implementing a pre-triage system offers a solution to deal with a surge in the number of patients who demand staff preparedness. This study aimed to determine the knowledge level on the pre-triage system and its relationship with the preparedness of emergency room staff in implementing the pre-triage system. The study was conducted with a cross-sectional approach in a private type C hospital in Malang District on all 30 ER staff as respondents. The research instrument used were questionnaires. Data analysis was done using descriptive analysis and the Fisher exact test. The results show that although 76.7% of respondents have insufficient knowledge, 86.7% of respondents are ready to implement the pre-triage system. The test results prove that there is no relationship between the knowledge and the preparedness levels of the emergency room staff in implementing the pre-triage system.